2005
DOI: 10.1021/nl048176c
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin Probe Force Microscopy Study on Conjugated Polymer/Fullerene Bulk Heterojunction Organic Solar Cells

Abstract: We conducted a comprehensive Kelvin probe force microscopy (KPFM) study on a classical organic solar cell system consisting of MDMO-PPV/PCBM blends. The KPFM method yields the information of topography and local work function at the nanometer scale. Experiments were performed either in the dark or under cw laser illumination at 442 nm. We identified distinct differences in the energetics on the surface of chlorobenzene and toluene cast blend films. Together with high-resolution scanning electron microscopy (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
265
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(282 citation statements)
references
References 50 publications
10
265
0
1
Order By: Relevance
“…31 During casting and subsequent annealing processes, there is a process of crystallization, alignment of polymer chains, and limited self-organization, which changes the structure to favor exciton collection and charge transport. 50,51 This process is extremely sensitive to the solvent used, 52,53 variations in composition, 54 annealing, [55][56][57][58][59] chemical-structure variations, [60][61][62][63] purities, 64 and processing conditions, 65 to name but a few of the related parameters when dealing with what is a fundamentally unstable system. 66 The seminal work by Yang et al demonstrated the necessity of controlled mixing of the acceptor and donor in the composite.…”
Section: Brief Overview Of Bulk-heterojunction Opvsmentioning
confidence: 99%
“…31 During casting and subsequent annealing processes, there is a process of crystallization, alignment of polymer chains, and limited self-organization, which changes the structure to favor exciton collection and charge transport. 50,51 This process is extremely sensitive to the solvent used, 52,53 variations in composition, 54 annealing, [55][56][57][58][59] chemical-structure variations, [60][61][62][63] purities, 64 and processing conditions, 65 to name but a few of the related parameters when dealing with what is a fundamentally unstable system. 66 The seminal work by Yang et al demonstrated the necessity of controlled mixing of the acceptor and donor in the composite.…”
Section: Brief Overview Of Bulk-heterojunction Opvsmentioning
confidence: 99%
“…It has been applied to characterize various types of solids used in electronic devices such as ionic crystal thin films, 2 semiconductors, 3 organic solar cell structures, 4 and nanographenes 5 in order to study the sample lateral variations of surface potentials and work functions and infer the electronic structures.…”
Section: Introductionmentioning
confidence: 99%
“…KPFM is a method working in combination with nc-AFM and which is based on the minimization of the electrostatic interaction between the tip and the sample. Electrostatic tip-sample interactions have been widely studied in the long-range regime on the experimental and on the theoretical level [23][24][25][26][27][28][29] within the frame of nc-AFM and KPFM [30][31][32][33][34] . Long-range electrostatic forces cause capacitive forces connected to the capacitance of the tip/counter-electrode capacitor as well as Coulombic forces connected to the presence of charges within it.…”
Section: Introductionmentioning
confidence: 99%